PHARMACEUTICO-ANALYTICAL STUDY OF CHAUSATHPRAHARI PIPPALI CHURNA (International Journal of Ayurveda and Pharma Research, 2021)
Ayurvedic pharmaceutics is one of the fastest growing sectors in the world market. Globalization expects pharmaceutical standardization. Competition in pharma industry expects good quality products which have documentation regarding safety and efficacy issues. Ancient heritage blended with current updated pharmaceutical technology helps in better appreciation. Chausath Prahari Pippali Churna is a classical Ayurvedic formualtion mentioned in Ayurvedsarasamghraha a renowned text of Ayurveda, which is useful in Vata and Kapha diseases. It has potent herbal remedy for both respiratory and digestive disorders. It is prepared by Bhavana with Phanta (hot infusion) of Badipippali to Chhotipippalichurna upto 64 Prahar (192hrs) to make it more strong and efficient formulation. The attempt is made in the present article to assess its pharmacological action and analytical aspect while processing the drug – Chausath Prahari Pippali Churna (CPP).